Microstructural Analysis of Stand Tyre Barrier: A Review of Blast-Induced Boundary Conditions - Aco Wahyudi Efendi (Nusantara Civil Engineering Journal, 2026)
This study evaluates the structural integrity of a Stand Tyre Barrier developed by PT. AWEfendi Geostruk Indonesia in Balikpapan, East Kalimantan, under static and blast loads. The barrier, designed to store large tires (CAT 777, 27.00R49), was analyzed using Finite Element Method (FEM) to withstand a static load of 1100 kg and dynamic blast energy of 1765 J. Key components included a 16 mm main plate, floor plate, and steel frame (angle 50×50×5 mm, UNP 150×75×6.5 mm, hollow 75×75×3.2 mm). Blast pressure was estimated at 86.3 kPa (incident) and 350 kPa (reflected peak). Results indicated maximum von Mises stress of 1791 kg/cm² (74.7% of allowable 2400 kg/cm² per SNI 03-1729-2002) and deformation of 0.011 cm (0.11 mm), confirming elastic behavior. Validations against experimental data (external work: 1765.4 kJ) confirmed model accuracy. The barrier meets safety standards but recommends material upgrades for larger-scale operations. This analysis provides a benchmark for blast-resistant industrial structures in high-risk environments.